Beacon Charter School Needs a School: A Case of Capital Outlay of Charters in a Public District. (September 2017) - Wronowski, Meredith L.
The case study presented below is a representation of a real-world, ongoing situation involving a public school district's capital outlay for charter schools within its boundaries. One particular charter, Beacon Charter School, was promised a permanent building by the public school district that also acts as its authorizer. However, recent events have created a statewide revenue failure which has, in return, caused a dramatic decrease in the school district's available funds. The school district leadership must decide whether they can still provide school facilities to Beacon Charter School. To complicate matters, the political climate surrounding the district's 12 charter schools has become increasingly contentious. This case study provides ample material for discussion as well as suggests guiding questions and activities.